Reflective activities of pupils with special educational needs and teachers in the self-educational process - Renata Geležinienė (Social Welfare: Interdisciplinary Approach, 2011)
The article considers reflective activities of pupils with special educational needs and teachers, analyzing experiences and meaningfulness of reflective activities. Data of the analysis of special educational needs pupils’ and teachers’ diaries are presented, emphasizing qualitative changes in teachers’ and pupils’ reflective activities.